Correction: Biohybrid plants with electronic roots via in vivo polymerization of conjugated oligomers. Issue 4 (25th March 2022) - Parker, Daniela; Daguerre, Yohann; Dufil, Gwennaël; Mantione, Daniele; Solano, Eduardo; Cloutet, Eric; Hadziioannou, Georges; Näsholm, Torgny; Berggren, Magnus; Pavlopoulou, Eleni; Stavrinidou, Eleni
Abstract : Correction for 'Biohybrid plants with electronic roots via in vivo polymerization of conjugated oligomers' by Daniela Parker et al., Mater. Horiz., 2021, 8, 3295–3305, DOI: ; 10.1039/D1MH01423D .